2017
DOI: 10.2139/ssrn.2926890
|View full text |Cite
|
Sign up to set email alerts
|

Stock Market Response to Potash Mine Disasters

Abstract: We examine the stock market reaction to natural and man-made disasters in potash mines. We use a sample of 44 mining accidents worldwide over the period 1995-2016. A quarter of the accidents were the result of a natural disaster, such as flooding, that often ended in the closure of the potash mine. The remaining accidents were caused mainly by human error, and almost 50% were work accidents often associated with serious injury or death. On average, mining firms experience a drop in their market value of 0.89% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 13 publications
0
29
0
Order By: Relevance
“…One further key argument that has recently been given much attention is related to different sources of financial volatility and major events that have affected stock market returns ( Zhu et al, 2019 , Corbet et al, 2020 , Zaremba et al, 2020 , Albulescu, 2020 , Onali, 2020 , Choudhry et al, 2016 , Demirer et al, 2019 , Wang et al, 2018 , Antonakakis and Darby, 2013 ). These sources of financial volatility are market uncertainty due to disasters ( Kowalewski and Śpiewanowski, 2020 , Liu et al, 2019 ; Papadamou et al, 2020 ), economic conditions and political events ( Bash and Alsaifi, 2019 ), institutional issues and social Media news ( Bollerslev et al, 2018 , Reboredo and Ugolini, 2018 ), environmental issues ( Alsaifi et al, 2020 ), information demand and investor attention ( Chronopoulos et al, 2018 , Nikkinen and Peltomäki, 2020 ), and pandemic diseases ( Chen et al, 2009 , Ichev and Marinč, 2018 ). In this strand, Albulescu (2020) examined the impact of official announcements regarding new cases of infection and death ratios on the financial market volatility index (VIX); and finds that the death ratio positively influences VIX.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…One further key argument that has recently been given much attention is related to different sources of financial volatility and major events that have affected stock market returns ( Zhu et al, 2019 , Corbet et al, 2020 , Zaremba et al, 2020 , Albulescu, 2020 , Onali, 2020 , Choudhry et al, 2016 , Demirer et al, 2019 , Wang et al, 2018 , Antonakakis and Darby, 2013 ). These sources of financial volatility are market uncertainty due to disasters ( Kowalewski and Śpiewanowski, 2020 , Liu et al, 2019 ; Papadamou et al, 2020 ), economic conditions and political events ( Bash and Alsaifi, 2019 ), institutional issues and social Media news ( Bollerslev et al, 2018 , Reboredo and Ugolini, 2018 ), environmental issues ( Alsaifi et al, 2020 ), information demand and investor attention ( Chronopoulos et al, 2018 , Nikkinen and Peltomäki, 2020 ), and pandemic diseases ( Chen et al, 2009 , Ichev and Marinč, 2018 ). In this strand, Albulescu (2020) examined the impact of official announcements regarding new cases of infection and death ratios on the financial market volatility index (VIX); and finds that the death ratio positively influences VIX.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the same vein, Chen and Chiang (2020) find evidence that a rise in economic policy uncertainty (EPU) leads to a decline in stock returns in the Chinese market. In the same line, Kowalewski and Śpiewanowski (2020) examined the stock market reaction to disasters; and find that the affected mining firms experience a cumulative drop in their market value of 1.15% in the first two days of a disaster.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Stock market returns respond to major events. Previous studies have identified several major events that have affected such returns, for example, disasters (Kowalewski & Śpiewanowski, 2020), sports (Buhagiar et al, 2018), news (Li, 2018), and environmental (Guo et al, 2020) and political events (Bash & Alsaifi, 2019;Shanaev & Ghimire, 2019). Stock market returns may also respond to epidemic diseases, for example, Severe Acute Respiratory Syndrome (SARS) outbreak (Chen et al, 2007;Chen et al, 2009), and Ebola Virus Disease (EVD) outbreak (Ichev & Marinč, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, as this virus becomes global pandemic, it starts effecting the businesses which is reflecting in world stock markets. Some studies have examined the impact of COVID‐19 on developed stock return (Al‐Awadhi, Al‐Saifi, Al‐Awadhi, & Alhamadi, 2020; Kowalewski & Śpiewanowski, 2020), which reported that the Hang Seng index and Shanghai stock exchange, United States and European stock markets reflect negative returns. In March, United States market hit by circuit brake mechanism, four times in 10 days.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, the studies are conducted in the developed economies to analyze the relationship between pandemic and stock exchanges (Al‐Awadhi et al, 2020; Kowalewski & Śpiewanowski, 2020). On contrary, we examine the impact of COVID‐19 on developing economy.…”
Section: Introductionmentioning
confidence: 99%